One way out [compact disc, unabridged] : the inside history of the Allman Brothers Band - Paul, Alan, 1966- (Tantor Media, 2014)
Alan Paul delivers the powerful biography of The Allman Brothers Band. An oral history written with the band's participation and filled with original, never-before-published interviews as well as personal letters and correspondence. This is the most in-depth look at a legendary American rock band that has meant so much to so many for so long.